2014
DOI: 10.3389/fnagi.2014.00195
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Personality Traits, Medial Temporal Lobe Atrophy, and White Matter Lesion in Subjects Suffering from Mild Cognitive Impairment

Abstract: Mild cognitive impairment (MCI) is a heterogeneous cognitive status that can be a prodromal stage of Alzheimer’s disease (AD). It is particularly relevant to focus on prodromal stages of AD such as MCI, because patho-physiological abnormalities of AD start years before the dementia stage. Medial temporal lobe (MTL) atrophy resulting from AD lesions and cerebrovascular lesions [i.e., white matter lesions (WML), lacunar strokes, and strokes] are often revealed concurrently on magnetic resonance imaging (MRI) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 55 publications
0
12
1
Order By: Relevance
“…[And as one might predict from these associations, within our cohort decreasing body mass index correlated with higher Conscientiousness (R2 = .045; p < .001)]. Higher Neuroticism in contrast has been shown to correlate with less healthy behaviors (Steptoe & Kivimaki, 2012;Terracciano & Costa, 2004), thus having the opposite effect on cognitive reserve and raising the testable hypothesis that personality factors may be associated with cerebrovascular contributions to cognitive reserve, a possibility for which there is already some evidence (Dermody et al, 2015;Duron et al, 2014). In addition, although a neuropathological correlate for Conscientiousness has not been found, higher Conscientiousness has been shown to be associated with an attenuated cognitive impact of dementia-related pathology especially terminally (Wilson, Boyle, Yu, Segawa, Sytsma, & Bennett, 2015).…”
mentioning
confidence: 57%
“…[And as one might predict from these associations, within our cohort decreasing body mass index correlated with higher Conscientiousness (R2 = .045; p < .001)]. Higher Neuroticism in contrast has been shown to correlate with less healthy behaviors (Steptoe & Kivimaki, 2012;Terracciano & Costa, 2004), thus having the opposite effect on cognitive reserve and raising the testable hypothesis that personality factors may be associated with cerebrovascular contributions to cognitive reserve, a possibility for which there is already some evidence (Dermody et al, 2015;Duron et al, 2014). In addition, although a neuropathological correlate for Conscientiousness has not been found, higher Conscientiousness has been shown to be associated with an attenuated cognitive impact of dementia-related pathology especially terminally (Wilson, Boyle, Yu, Segawa, Sytsma, & Bennett, 2015).…”
mentioning
confidence: 57%
“…In a population-based cohort of over 500 older adults, for example, low conscientiousness was associated with measures of whole brain integrity, including brain-tissue loss and white matter hyperintensities (Booth et al, 2014). In samples with mild cognitive impairment, lower levels of conscientiousness and higher levels of neuroticism have been associated with white matter lesions (Duron et al, 2014). A prospective study with an autopsy component (Terracciano et al, 2013) found that higher neuroticism and lower agreeableness were significantly associated with advanced neurofibrillary tangles stages, one hallmark of Alzheimer’s neuropathology.…”
Section: Discussionmentioning
confidence: 99%
“…Premorbid personality may thus be acting as a determinant factor so that the original personality changes as AD advances (Welleford et al, 1995). Furthermore, lower consciousness and higher neuroticism is also associated with greater vulnerability to metabolic syndrome (Sutin et al, 2010a), inflammatory risk profile (Sutin et al, 2010b), smaller volume of medio-temporal and prefrontal regions and greater decline in volume with advancing age (Jackson et al, 2011), and with severity of white matter lesions in MCI patients (Duron et al, 2014). While premorbid personality characteristics may influence the risk of developing cerebral pathology and related cognitive impairment, changes in personality may represent the adaptive reaction to the individual's experience of cognitive and functional impairment or may be more directly related to developing cerebral pathology, or both.…”
Section: Discussionmentioning
confidence: 99%